Exploring the social and emotional impact of COVID-19 on older residents of the Greater Klang Valley, Malaysia: A qualitative study - Mirchandani Shobha; Karen Morgan; Maw Pin Tan (PLoS ONE, 2025)
Background The Coronavirus Disease 2019 (COVID-19) pandemic and associated public health measures significantly disrupted the lives of older adults. Few studies have captured the firsthand experiences of this population during such unprecedented times, emphasizing the need for qualitative insights into their lived realities. This study aimed to explore the social and emotional impact of the COVID-19 pandemic on older adults, focusing on personal experience, coping mechanisms, and adaptive responses to changes. Methods A qualitative research design was employed, utilizing snowball sampling to recruit participants aged 60 years and above. Semi-structured interviews were conducted to collect in-depth narratives about participants’ experiences post-pandemic, between May 2023- March 2024. Data were analysed using thematic analysis to identify recurring patterns and meaningful themes. Results A total of 19 participants (aged 60–81 years, 10 women) were interviewed. Four themes emerged from the study: 1) emotional and psychological symptoms linked to infection control; 2) feeling of loss from restrictions; 3) coping strategies in adversity; 4) information and communication. Participants relied on their resilience and life experiences to navigate fear and uncertainty during the pandemic. Conclusion The identified themes reflect a collective experience of fear, loss, adaptation and resilience. Support systems and adaptability demonstrated by individuals underscored the capacity to cope with and overcome adversity. A good social security system post-retirement is hard to achieve in low and middle income countries. Future research should utilize fundings to focus on providing targeted support to older adults and other LMICs to develop mitigation strategies to prevent negative psychological, physical and financial effects in major disasters.